Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
- 16
Step-by-step explanation:
Given:
- f(x) =3x - 8 and g(x) = x² + 4
- f(g(- 2)) = ?
First find g(- 2):
- g(- 2) = (-2)² + 4 = 4 + 4 = 8
Find f(8):
- f(8) = 3*8 - 8 = 24 - 8 = 16
g(-2):-
[tex]\\ \sf\longmapsto (-2)^2+4[/tex]
[tex]\\ \sf\longmapsto 4+4[/tex]
[tex]\\ \sf\longmapsto 8[/tex]
Now
[tex]\\ \sf\longmapsto f(x)=3x-8[/tex]
[tex]\\ \sf\longmapsto f(g(-2))=f(8)[/tex]
[tex]\\ \sf\longmapsto 3(8)-8[/tex]
[tex]\\ \sf\longmapsto 24-8[/tex]
[tex]\\ \sf\longmapsto 16[/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.